Effects of methane steam reforming on the mechanical stability of solid oxide fuel cell stack. (15th September 2022) - Guo, Meiting; Ru, Xiao; Yang, Lin; Ni, Meng; Lin, Zijing
Highlights: Mechanical performance study of a large-scale SOFC stack. Thermal load obtained by multiphysics coupling model. Thermal stress distribution characteristic and underlying mechanism revealed. The effect of methane steam pre-reforming ratio on mechanical failure evaluated. Abstract: Thermal stress-induced mechanical failure is a critical issue for practical application of solid oxide fuel cells (SOFCs). Due to the lack of study on the thermo-mechanical behavior of SOFC with different methane steam pre-reforming ratios (R), a 3D thermo-mechanical model is developed to systematically evaluate the mechanical performance of SOFC running on methane fuel. The model fully considers the coupled transport and reaction processes in the SOFC. The numerically obtained temperature is imported to a mechanical sub-model to determine the thermal stress and strain of SOFC components under various operating conditions, namely with different R values. Covering all R conditions, glass–ceramic sealant is the most dangerous component, while cathode is in sub-critical state. When R < 0.4, the electrolyte has the minimum failure probability. When R > 0.4, the anode becomes the safest component in SOFC stack. With the increase of R, the failure probability of anode decreases all the way and always stays in the safe range, while first decreases then increases for electrolyte, cathode and sealant. R within range of 0.4–0.7 is favorable for the reliability of the whole SOFC stack. This study is useful for identifying optimal operating conditions for efficient and stable operation of SOFC running on alternative hydrocarbon fuels.